Tafsir Maqasidi and Islamic Legal Reasoning in the Tolerance Practices of Muslim Minorities in North Sulawesi - Ahmad Yusam Thobroni; Iskandar Zainuddin; Syamsudin Syamsudin; Sulthon Mas'ud; Ahmad Fathan Aniq (Jurnal Ilmiah Al-Syir'ah, 2026)
This article examines how Muslim minority communities in North Sulawesi negotiate Islamic legal norms of tolerance within a predominantly Christian social environment. It argues that tolerance is not merely moral accommodation, but a form of contextual Islamic legal reasoning derived from a maqasidi reading of Qur’anic values and developed through maqasid al-shariah. This empirical-normative Islamic legal study uses juridical-sociological, Tafsir Maqsidi, and maqasid al-shariah approaches. Primary data were obtained through interviews with 15 informants in Manado, North Minahasa, and Bitung, supported by participatory observation and documentation. The findings show that tolerance is constructed through three spaces. In religious spaces, Muslims attend interfaith ceremonial events while avoiding participation in non-Muslim worship, reflecting hifz al-din. In cultural spaces, they selectively engage with local traditions such as Mapalus, Tulude, and thanksgiving practices, accepting elements compatible with Islamic values and avoiding those contrary to Islamic belief. In social spaces, cooperation in welfare, disaster relief, security, and civic activities reflects hifz al-nafs, hifz al-mal, hifz al-’ird, and maslahah ‘ammah. The study contributes to Islamic legal studies by showing how Tafsir Maqsidi connects Qur’anic values of tolerance with maqasid-based legal adaptation in Muslim minority contexts.